The effect of LED light color and feed type on the performance of male broiler chicks to 21 days - McGurk, Kayla; Delfelder, C.J.; Seitz, Daniel E.; Beyer, R. Scott (My University, 2017)
Poultry producers are rapidly adapting new lighting technology that reduces labor and energy costs. There are numerous choices of color or spectrum, brightness, control systems, and lenses available in the marketplace. These choices will impact energy use, bird performance, and animal welfare as well as farm workers. Intensity and color may impact how a bird views the water and feed devices, litter, and other birds. Birds are able to distinguish subtle differences in feed texture and will choose feed pellets, crumbles and fines and will select a preferred form. Feed color is influenced by ingredients and additives. Newly placed chicks must locate feed and water soon after placement. A study was designed to determine broiler prestarter and starter performance when placed under 4 colors of lights: red, green, blue, and white and two feed types: sorghum-soy or corn-soy based in a 4 by 2 factorial arrangement with 4 reps for each combination of treatments. Pens were fitted with LED focal lights 72” over the litter, with the ring of light focused between the feed pan and the nipple drinker line. The pens were 5’ by 14’ with 4” of pine shavings. Twelve male Cobb broiler chicks were placed in each pen which was randomly assigned a light color and feed type. Two diets, similar in nutrient content but either corn or sorghum-based, were formulated to meet the recommended requirements and fed in a mash form with a similar texture. The diet phases were 10d and 21d for the prestarter and starter rations respectively. At placement, house incandescent lights at 25 lumens were provided for 48 hours, then reduced to 15 lumens for 24 hours. On day 4, the house lights were extinguished and only the LED lamps were used, and were set at 15 lumens in the focal area. Pen weights and feed were recorded at day 10 and 21. The results indicate that at 10d, sorghum fed chicks were significantly less feed efficient than corn fed chicks, however, no other measurement in the study was affected by diet type. At 10d, only the chicks under blue light had increased BWG. The chicks under blue lights fed corn were significantly more efficient. Throughout the remainder of the study, there were no main effects of light color, feed type, or interaction observed for any of the treatments. The results indicate that under blue, red, green or white lights, early performance of male broiler chicks are remarkably similar.
Keywords: Spring 2017